ANALISIS KESALAHAN HASIL UJIAN AKHIR SEMESTER MATEMATIKA SISWA MTs Hi HAYYUN SALUMPAGA TAHUN AJARAN 2022/2023 BERDASARKAN PROSEDUR NEWMAN: Analysis of Error Analysis of Mathematics Final Examination Results of Mts Students Hi Hayyun Salumpaga For Academic Year 2022/2023 Based on Newman Procedure - Rauf, Mutia A; Karniman, Tegoeh S.; Rizal, Muh.; Fajriani (Universitas Tadulako, 2024)
This study aims to obtain a description of student errors in the results of the mathematics final exams for the 2022/2023 school year based on the Newman Procedure. This type of research is qualitative. The research subjects used in this study were 29 students of class IX B MTs Hi Hayyun Salumpaga. The results of this study are in the form of descriptions of student errors and the causes of errors made by class IX B MTs Hi Hayyun Salumpaga. Based on the research results, it has been found that the most dominant errors are process errors with a percentage of 77%, transformation errors with a percentage of 82%, errors in understanding the problem with a percentage of 75%, and errors in writing the final answer with a percentage of 72%. The mistakes made in (1) the error in understanding the problem is where students do not write down what is known and what is asked, (2) transformation errors that occur, namely students misunderstand the meaning or concept to be used, (3) the process error made was not being able to carry out the process correctly and not being thorough, (4) errors in writing the final answer, namely the student made a mistake in writing the final answer and got an incorrect answer.